Fruit beverages processed using ultrasound technology: physical properties, stability and enzyme inactivation - Rojas Silva, Meliza Lindsay (2016)
This work studied the improvement of stability, physical properties and enzymatic inactivation in fruit beverages by applying the ultrasound technology (US). In the first part, the effect of the US application on peach juice processing was evaluated. The macroscopic changes on pulp sedimentation stability, turbidity, colour and rheological properties were evaluated. As a result, it was demonstrated that the improvement in each of the properties evidenced at the macroscopic level involves interaction of complex mechanisms which depend directly on changes at the microscopic level, such as the structure, size, composition and interaction between the continuous phase (serum) and dispersed phase (pulp) of the juice. These changes were assessed by microscopy and particle size distribution. In the second and third parts, the inactivation of the enzyme peroxidase (POD) was evaluated in coconut water. In the second part, the effect of the application of US was evaluated for first time for coconut water POD, using two types of ultrasonic equipment (US baht and US probe). It was demonstrated that the changes of enzyme activity during the US process depend on the many forms that the enzyme can adopt, mainly depending on the energy applied to the system. Subsequently, in the third part, the US was applied as a pre-treatment of subsequent thermal processing. The evaluation was carried out under non isothermal conditions, being the POD inactivation kinetics modelled using the Weibull distribution function. Finally, it was observed that the pre-treatment using ultrasound slightly decreased the enzyme activity. Furthermore, the ultrasound effects resulted in a more homogeneous population and heat-sensitive enzymes, significantly reducing the needed time of thermal processing. In conclusion, this work studied and demonstrated that the ultrasound technology is an interesting alternative to improve the physical properties and enzymatic stability in fruit beverages, reflecting the importance from both the academic and industrial point of view.